2017
DOI: 10.1097/md.0000000000006640
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory member of the apoptosis-stimulating protein of p53 is overexpressed in bladder cancer and correlated to its progression

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Indeed, there is growing evidence that overexpression, rather than mutation, of iASPP conveys its oncogenic properties. In addition to our previous characterization in p53 wild-type breast cancer (32), elevated iASPP levels have recently been reported in multiple human cancers, including bladder cancer (63), non-small-cell lung cancer (64), ovarian clear cell carcinoma (65), colorectal cancer (66), and particularly in acute leukemia where p53 mutations are relatively rare (67, 68).…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, there is growing evidence that overexpression, rather than mutation, of iASPP conveys its oncogenic properties. In addition to our previous characterization in p53 wild-type breast cancer (32), elevated iASPP levels have recently been reported in multiple human cancers, including bladder cancer (63), non-small-cell lung cancer (64), ovarian clear cell carcinoma (65), colorectal cancer (66), and particularly in acute leukemia where p53 mutations are relatively rare (67, 68).…”
Section: Discussionmentioning
confidence: 65%
“…It reduced damaged cell death and accumulated injuries in cells, which was beneficial for tumour survival. According to our results, low ASPP2 expression independently predicted poor prognosis of ESCC patients, which is consistent with previous reports of other cancers [22,23]. The results of qRT-PCR in this study demonstrated that the relative expression of ASPP2 mRNA was markedly downregulated in ESCC samples compared with the paired tumor adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq and p53 ChIP-seq analyses have confirmed that many iASPP/p53 coregulated targets are involved in regulating apoptosis, consistent with iASPP as an evolutionarily conserved inhibitor of p53-mediated apoptosis [ 6 , 7 ]. Evidence to date suggests that iASPP is an oncoprotein, as high expression of iASPP associates with poor prognosis in ovarian, melanoma, prostate, glioma and bladder cancers [ 8 12 ]. In vitro and xenograft studies have shown that iASPP has pro-proliferative and chemoresistant properties.…”
Section: Introductionmentioning
confidence: 99%